Bifunctional Molecular Photoswitches Based on Overcrowded Alkenes for Dynamic Control of Catalytic Activity in Michael Addition Reactions - Pizzolato, Stefano F.; Collins, Beatrice S. L.; van Leeuwen, Thomas; Feringa, Ben L. (Chemistry : a European journal, 2017)
The emerging field of artificial photoswitchable catalysis has recently shown striking examples of functional light‐responsive systems allowing for dynamic control of activity and selectivity in organocatalysis and metal‐catalysed transformations. While our group has already disclosed systems featuring first generation molecular motors as the switchable central core, a design based on second generation molecular motors is lacking. Here, the syntheses of two bifunctionalised molecular switches based on a photoresponsive tetrasubstituted alkene core are reported. They feature a thiourea substituent as hydrogen‐donor moiety in the upper half and a basic dimethylamine group in the lower half. This combination of functional groups offers the possibility for application of these molecules in photoswitchable catalytic processes. The light‐responsive central cores were synthesized by a Barton–Kellogg coupling of the prefunctionalized upper and lower halves. Derivatization using Buchwald–Hartwig amination and subsequent introduction of the thiourea substituent afforded the target compounds. Control of catalytic activity in the Michael addition reaction between (E)‐3‐bromo‐β‐nitrostyrene and 2,4‐pentanedione is achieved upon irradiation of stable‐(E) and stable‐(Z) isomers of the bifunctional catalyst 1. Both isomers display a decrease in catalytic activity upon irradiation to the metastable state, providing systems with the potential to be applied as ON/OFF catalytic photoswitches. Clap on, clap off: The synthesis of two bifunctional molecular switches and the experimental study of their photochemical and catalytic behaviour is presented. Dynamic control of catalytic activity of the Michael addition reaction is achieved upon irradiation of stable‐(E)‐1 and stable‐(Z)‐1. This demonstrates that both isomers display a decrease in catalytic activity upon irradiation to the metastable state, providing systems with the potential to be applied as ON/OFF catalytic photoswitches.